1976
DOI: 10.1021/j100548a014
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance study of radiation-induced radicals from maleic anhydride in irradiated frozen solutions

Abstract: Radicals produced from maleic anhydride in 7-irradiated frozen solutions of 2-methyltetrahydrofuran have been identified by their ESR spectra. The initial product is the molecular anion radical I. During thermal annealing at 98 K, radical I converts into the protonated anion II and the X-addition radical IV is formed supposedly from the addition of the solvent radical to the remaining solute molecule. Evidence for X ^H is obtained from the comparison with the spectrum of III produced by loss of an hydrogen ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…It is difficult to assign the radical structure produced by the mechanochemical reaction of PMMA with MA from these data obtained. Fukaya et al observed the ESR spectra of MA radicals produced by γ-irradiation at 77 K [27], which were not a broad singlet and apparently different from those obtained in this experiment. Tion et al reported that MA radicals produced by mechanochemical reaction of copolymer of MMA and MA (poly(MMA-co-MA)) at -55 ºC disappeared with spectral changes at 0 ºC [28].…”
Section: Esr Spectra Observed In Mechanochemical Reaction Of Pmma and Macontrasting
confidence: 86%
“…It is difficult to assign the radical structure produced by the mechanochemical reaction of PMMA with MA from these data obtained. Fukaya et al observed the ESR spectra of MA radicals produced by γ-irradiation at 77 K [27], which were not a broad singlet and apparently different from those obtained in this experiment. Tion et al reported that MA radicals produced by mechanochemical reaction of copolymer of MMA and MA (poly(MMA-co-MA)) at -55 ºC disappeared with spectral changes at 0 ºC [28].…”
Section: Esr Spectra Observed In Mechanochemical Reaction Of Pmma and Macontrasting
confidence: 86%